(untitled) (World Bulletin of Social Sciences, 2026)
The organization of psychological services in the preschool education system plays an important role in supporting the mental, emotional, and social development of children. Psychological services help identify children’s individual characteristics, learning needs, and possible developmental difficulties at an early stage. The main tasks of psychological services include providing psychological support to children, assisting educators and parents in understanding children’s behavior and emotional state, and creating a favorable psychological environment in preschool institutions. In addition, psychologists contribute to the development of children’s cognitive abilities, communication skills, and social adaptation. Effective organization of psychological services ensures the healthy development of preschool children and improves the overall quality of the educational process